THE CIVILIZATIONAL ASPECTS OF INTERACTING WITH CHRISTIANS IN THE PROPHETIC ERA: AN ANALYTICAL STUDY BASED ON THE BOOK ’ZAD AL-MA’AD FI HADI KHAYR AL-’IBAD’ BY IBN AL-QAYYIM AL-JAWZIYYA - Ubaid Ullah Sindhi; Dr. Abdul Qadir Abdul Kareem Gondal (Journal of Religion and Society, 2025)
This study explores how Prophet Muhammad ﷺ treated Christians during his time, based on the book Zad al-Ma'ad by Ibn al-Qayyim. It highlights the principles of inviting Christians to Islam, such as his letter to the Roman Emperor and his discussions with the Najran delegation. The study also examines rules followed during battles, like respecting messengers, making peace agreements, and managing taxes. Additionally, it looks at the moral and legal principles in the Prophet’s dealings with the Christians of Abyssinia and Najran, including religious freedom, protection of wealth, fairness, and keeping promises. Keywords: Interfaith Dialogue, Diplomacy, Religious Freedom, Moral and Legal Principles.